Natural killer cells in NOD.NK1.1 mice acquire cytolytic function during viral infection and provide protection against cytomegalovirus - Orr, Mark T. (National Academy of Sciences, 2010)
Resting natural killer (NK) cells in nonobese diabetic (NOD) mice have impaired immune functions compared with NK cells from other mouse strains. Here we investigated how NOD NK cells respond after mouse cytomegalovirus (MCMV) infection, using NOD mice congenic for the protective NK gene complex from C57BL/6 mice. Compared with C57BL/6 mice congenic for the H2 gene complex from NOD mice (B6.g7), NOD.NK1.1 mice fail to control early infection with MCMV. After MCMV infection, however, NOD.NK1.1 NK cells demonstrate increased cytolytic function, associated with higher expression of granzyme B, and undergo robust expansion. One week after infection, NOD.NK1.1 NK cells control MCMV replication as effectively as B6.g7 NK cells, even in the absence of T cells and B cells. Thus, the impaired cytotoxic function of NK cells in NOD mice is alleviated by viral infection, which enables NOD NK cells to efficiently control MCMV infection.